A Case of Chronic Calcific Nonalcoholic Pancreatitis - Aaron Kangas-Dick; Umair Khan; Oluwafunbi Awoniyi; Shanza Waqar; Nu Nwe Tun; Karthikeyan Viswanathan; Cynthia Wong (Case Reports in Gastrointestinal Medicine)
Tropical Calcific Pancreatitis (TCP) is a type of chronic calcific nonalcoholic pancreatitis. Similar to nonalcoholic chronic pancreatitis, it presents in the second and third decades of life; however this type is reported mostly in the developing tropical and subtropical countries. It is associated with the formation of pancreatic calculi and a high probability of developing insulin-dependent diabetes mellitus. Epidemiologic studies have shown that these patients have an increased risk of developing pancreatic carcinoma. The etiology of TCP remains uncertain, with the current consensus suggesting genetics as well as possible toxicity from consuming large amounts of cassava, a tuber. Definite diagnosis of TCP requires younger age of onset, history of malnutrition, and presence of diabetes mellitus along with extensive pancreatic calcification and ductal calculi. When patients meet most but not all of these conditions the term Idiopathic Chronic Pancreatitis (ICP) is used. This is a case of a 44-year-old man who presented with most features seen in TCP, and however, was diagnosed with ICP.